HER+ Second high-level dialogue meeting on gender and climate change in South Asia, October 13, 2023. - Shoby Michael; Milan Shobi (CGIAR GENDER Impact Platform, 2023)
The second high-level dialogue meeting convened by CGIAR gender equality research initiative, HER+ in New Delhi on October 13, 2023, facilitated knowledge exchange on challenges and solutions for gender equality and climate resilience in agrifood systems across India and the wider South Asia region. It welcomed stakeholders from various sectors—government officials, farmer representatives, gender and climate experts, researchers, the private sector, and donors.